The aPKC-CBP Pathway Regulates Post-stroke Neurovascular Remodeling and Functional Recovery - Gouveia, Ayden; Seegobin, Matthew; Kannangara, Timal S.; He, Ling; Wondisford, Fredric; Comin, Cesar H.; Costa, Luciano da F.; Béïque, Jean-Claude; Lagace, Diane C.; Lacoste, Baptiste; Wang, Jing (Université d'Ottawa | University of Ottawa, 2017)
Epigenetic modifications have emerged as attractive molecular substrates that integrate extrinsic changes into the determination of cell identity. Since stroke-related brain damage releases micro-environmental cues, we examined the role of a signaling-induced epigenetic pathway, an atypical protein kinase C (aPKC)-mediated phosphorylation of CREB-binding protein (CBP), in post-stroke neurovascular remodeling. Using a knockin mouse strain (CbpS436A) where the aPKC-CBP pathway was defective, we show that disruption of the aPKC-CBP pathway in a murine focal ischemic stroke model increases the reprogramming efficiency of ischemia-activated pericytes (i-pericytes) to neural precursors. As a consequence of enhanced cellular reprogramming, CbpS436A mice show an increased transient population of locally derived neural precursors after stroke, while displaying a reduced number of i-pericytes, impaired vascular remodeling, and perturbed motor recovery during the chronic phase of stroke. Together, this study elucidates the role of the aPKC-CBP pathway in modulating neurovascular remodeling and functional recovery following focal ischemic stroke.
Keywords: aPKC-CBP pathway; cellular reprogramming; ischemic stroke; neural precursors; pericyte; vascular remodeling; Animals; Brain Ischemia; CREB-Binding Protein; Cellular Reprogramming; Mice; Neurogenesis; Pericytes; Phosphorylation; Protein Kinase C; Recovery of Function; Signal Transduction; Stroke; Stroke Rehabilitation; Vascular Remodeling